1997
DOI: 10.1300/j013v25n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use with Main Partners by Sterilized and Non-Sterilized Women

Abstract: This study examined condom use with main partners by surgically sterilized and non-sterilized women at risk for HIV infection. Data were obtained from 379 African American women residing in low-income urban communities. Sterilized women were one-fifth as likely as non-sterilized women to use condoms. Multivariate logistic regression indicated that for both groups of women, higher perceived benefits of condom use for disease prevention were associated with condom use. In addition, younger age, self-efficacy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Sangi-Haghpeykar, Posner, and Poindexter (2005) reported that surgically sterile women were significantly less likely than hormonal contraceptive users to have used condoms. The study conducted in surgically sterilized and non-sterilized women at risk for HIV infection found that sterilized women were one-fifth as likely as non-sterilized women to use condoms (Semaan, Lauby, & Walls, 1997). Thus, in general we believe that among married women the level of condom use is inversely related to the perceived efficacy of a contraceptive method.…”
Section: Discussionmentioning
confidence: 93%
“…Sangi-Haghpeykar, Posner, and Poindexter (2005) reported that surgically sterile women were significantly less likely than hormonal contraceptive users to have used condoms. The study conducted in surgically sterilized and non-sterilized women at risk for HIV infection found that sterilized women were one-fifth as likely as non-sterilized women to use condoms (Semaan, Lauby, & Walls, 1997). Thus, in general we believe that among married women the level of condom use is inversely related to the perceived efficacy of a contraceptive method.…”
Section: Discussionmentioning
confidence: 93%
“…A study of 2864 women “at risk” for HIV infection demonstrated as risk factors for poor use exchanging sex for money or drugs, binge drinking, having limited resources, and being dependent on one’s partner (124). A study of women who had a tubal ligation demonstrated an extremely poor rate of condom use in this population, with only one-fifth as many using condoms as demonstrated in unsterilized women (125). …”
Section: Contraceptionmentioning
confidence: 98%
“…A study of 2864 women "at risk" for HIV infection demonstrated as risk factors for poor use exchanging sex for money or drugs, binge drinking, having limited resources, and being dependent on one's partner (124). A study of women who had a tubal ligation demonstrated an extremely poor rate of condom use in this population, with only onefifth as many using condoms as demonstrated in unsterilized women (125).…”
Section: Contraceptionmentioning
confidence: 98%